Heterocycle-appended lanthanum(III) sandwich-type (porphyrinato)(phthalocyaninates). (October 2020) - Birin, Kirill P.; Abdulaeva, Inna A.; Poddubnaya, Anna I.; Gorbunova, Yulia G.; Tsivadze, Aslan Yu.
Abstract: An approach to a new type of heteroleptic triple-decker lanthanide (porphyrinato)(phthalocyaninates) bearing functionalized heterocycle-appended low-symmetry porphyrin ligands is developed. The first representatives of such sandwich-type complexes based on porphyrins fused with imidazole or pyrazine cycle are synthesized and precisely characterised. The influence of the nature of the appended 5- or 6-membered heterocyclic fragments onto the electronic properties of complexes is revealed by means of UV–vis spectroscopy. It is found, that the annulation of pyrazine heterocycle results in the expansion of the aromatic system of the ligand, while the annulation of imidazole reveals vanishing influence onto the electronic structure of the molecule. The structural peculiarities originating from the low symmetry of the prepared sandwich-type complexes is investigated in details by NMR. Graphical abstract: Image 1 Highlights: New type of heteroleptic triple-decker lanthanide (porphyrinato)(phthalocyaninates). Heterocycle-appended low-symmetry porphyrin ligands. Influence of the nature of the appended 5- or 6-membered heterocycle onto the electronic properties of complexes. NMR investigation of structural peculiarities originating from the low symmetry of the prepared complexes.